The effect of role overload, role ambiguity, autonomy and fairness of reward on employees job satisfaction level among office worker / Siti Nur Najihah Sairan - Sairan, Siti Nur Najihah (Faculty of Business and Management, 2017)
Job satisfaction is a very important matter for organization towards their employees. It involved people’s feeling about their work especially employees who experience more challenging work. When employee feel not satisfied with the organization, it can increase employees stress and that can be a big problems towards the organization. This paper investigates some of the factors that can affect employees’ job satisfaction at work among office worker. Office worker deal with creative and professional skills of work and they normally felt pressure. This study used main data collection method by using a questionnaire from office worker at Bangunan Sultan Ismail, Pontian Johor that consists Pejabat Daerah Pontian and Pejabat Tanah Pontian to determine the significant factors that can affect employees’ job satisfaction at work. The total population is 135 employees and from the total population, the sample size of 97 respondents was chosen from using convenience sampling. The finding of this study for independent variable “Role Overload” and “Role Ambiguity” has support the hypothesis and significantly related to the job satisfaction at work but the correlation result indicate that role overload and role ambiguity has negative influence with the job satisfaction. Hence, in order to increase the employee’s job satisfaction at work, all management should work together to find the best factors in maintaining their employees. For further study, it is suggested to change the factors and places where study is conducted.